Characterization of serratia spp. from water and sediment from aquaculture environment - Nurul Ain, Bt. Abdul Mattin (Universiti Malaysia Sarawak (UNIMAS), 2011)
Serratia spp. are classified under Enterobacteriaceae and the pathogenic species. Serratia marcescens is notoriously associated with nosocomial infection in patients. In this study, Serratia spp. were isolated from water and sediment samples. The sampling was carried out at a pond in Samariang and 7U1 Mile, Kuching. Further identification and confmnation tests were carried out using TSI test, citrate utilization test, catalase test, urease test, MRVP test, gram staining and DNA sequencing. (GTG)s-PCR was conducted to analyze the genetic diversity of species isolated. II isolates of the Serratia spp. were characterized by antibiotic susceptibility testing and DNA profiling using (GTG)sPCR. In antibiotic susceptibility testing, the antibiotics used were ampicillin, vancomycin, bacitracin, nitrofurantoin, norfloxacin, kanamycin, erythromycin. chloramphc!nicol, streptomycin, tetracycline, nalidixic acid, sulphamethoxazole/trimethoprim, gentamycin and carbenicillin. All isolates were resistant to vancomycin, bacitracin, nitrofurantoin, erythromycin and chloramphenicol. The phylogenetic tree constructed for DNA fingerprinting using (GTG)5-PCR technique indicates that Serratia spp. isolated from the water and sediment samples were genetically diverse and the isolates showed multiple-resistance to the antibiotics being tcsted.